Estrategia de difusión del patrimonio histórico de Puebloviejo para el desarrollo del turismo cultural - Sarabia Fajardo, Nohely Dayana (2021)
This research will analyze the Strategy for the Dissemination of the Historical Heritage of the Puebloviejo Canton, for the Development of Cultural Tourism in the Canton Puebloviejo Province of Los Ríos detailing in summary the strategy of dissemination of historical heritage for development of Cultural Tourism. The case study possesses the following research methodology as diagnostic research, descriptive research and exploratory research of diagnostic research result in cultural physiognomic diversity that goes parallel with the descriptive methodology and the exploratory methodology is the one that leads to the collection of data of all the inescapable information for the development of this case study. With the collection of data on the Documentary Historical Heritage, the technique will be applied of the online survey, allowing to know the significance of the Socialization Documentary Historical Heritage of the Puebloviejo Canton Province of Los Ríos.